Heterogeneous effect of exchange rates on firms' exports: Role of labor intensity - Kurmaş Akdoğan; Yusuf Kenan Bağır; Huzeyfe Torun (Central Bank Review (CBR), 2023)
Using an extensive firm-level database that combines balance sheet information, social security registry and customs data, we examine whether the relationship between the exchange rate and exports change with the degree of labor-intensity of production. The results based on manufacturing firms in Türkiye suggest that the sensitivity of labor-intensive firms to the exchange rate is higher than that of the less labor-intensive ones, both at the intensive and extensive margins of exports. In addition, export product variety and export market variety of the labor-intensive firms increase more than the others during a currency depreciation. In particular, the increase in the exports of the labor-intensive firms is 2.7 percent higher than the increase in exports of the non-labor-intensive firms in case of a 10 percent decline in the real effective exchange rate. However, we do not find a significant impact on the export prices varying across the labor-intensity of the firms. Our results are robust to alternative definitions of labor-intensity and exchange rates, and the use of different time spans.
Keywords: F14; F16; D22; 330; Exports; Exchange rates; Labor-intensity